Células mesenquimais adultas derivadas de tecido adiposo na distração osteogênica da mandíbula em coelhos pós radiação ionizante - Soares, Marcelo Melo [UNIFESP] (2016)
The aim of this study is to evaluate the effect of adipose derived mesnchymal stem cell (ADSC) on the regeneration of distraction osteogenesis on irradiated mandible of adult rabbit.Ten adult rabbits were selected and the dorsal fat penicle was removed for harvesting and culture of adipose derived adult mesenchymal stem cells. The mandibles were irradiated on a single dose of 20Gy. After 30 days the animals underwent to mandibular lengthening by distractions osteogenesis. After 10mm of mandibular lengthening, the animals were divided on two groups. On the control group, 1 ml of saline solution was injected and on the study group, and ADSC (1 x 106 ) was injected in the study group. After consolidation phase ( 4 weeks) the mandibles were removed and evaluated by tomography. The spiceaments were cuted in slices (7-?m per slice) forhistological evaluation. The sections were stained with Mallory trichome and assessed under a light microscope. Histomorphometric were analysed using J image program and stataistc analyses obtained by Mann-Withney test (p>0,05).The tomography shows a significant improvement on Hounsfield scale (ZFVL on GC 114,5 and GE 148 p= 0.0,0045* / ZFVC, 37, on GC to 96 GE,p=0.0045*).The Histomorphometric analysis demonstrated increase on the mineralized tissue occupation by new bone formation (ZFVD 37,5% on GC to 75.9% on GE p=0.0002*, ZFVM 39,1% on GC to 79,1% on GE p=0,0001*, ZFVC, 31,3% on GC to 61,2% no GE p= 0.045*) The results achived, showed a significative increase on bone formation on fibrovascular zone (z=2.61 and p=0.0045).The injection of adipose derived mesenchymal stem cell is able to improve bone regeneration on irradiated distraction callus on rabbit mandible.